HIPC assistance from Trinidad and Tobago : a creditor's perspective - Ramirez, Susan (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Traces the evolution of Guyana's indebtedness to Trinidad and Tobago both as its bilateral creditor and multilateral creditor under the CARICOM Multilateral clearing Facility.